Public speaking and personal branding skills for student organization managers at Dharma Wanita High School Surabaya - J. Juwito; Zainal Abidin Achmad; Ira Kaestiningtyas; Prahasti Ken Dewani; Dwi Wahyuningtyas; Ramadhani Mahendra Kusuma; Kusuma Wardhani Mas’udah; Tria Puspa Sari; Roziana Febrianita (Universitas Muhammadiyah Malang, 2022)
Self-confidence Not everyone has good self-confidence. Therefore, it needs to be encouraged in several ways: through public speaking combined with personal branding. The purpose of this service was to develop public speaking and personal branding skills for student organization managers at SMA Dharma Wanita Surabaya through the PIKAT scheme. The training is divided into two; offline and online. The training program is carried out by carrying out counseling on public speaking and personal branding based on theories in communication. The second activity is to train public speaking and personal branding where the participants can practice their public speaking skills. Monitoring after mentoring and training activities is still carried out. At the end of the program, there are four outputs/recommendations, training modules, activity news, and community service journals. It can be concluded that this activity encourages the development of public speaking and personal branding skills for student organization managers at SMA Dharma Wanita Surabaya.